ASSOCATION BETWEEN PSORIASIS AND CELIAC DISEASE : A SYSTEMATIC REVIEW - Fitriana, Ilma (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Psoriasis is an inflammatory illness that affects the skin and is characterised by the formation of erythematous and scaly plaques. Psoriasis is a chronic condition. Psoriasis vulgaris, often known as plaque psoriasis, is the most common form of psoriasis; however, there are many other types of psoriasis as well. Psoriasis vulgaris is the most common form of psoriasis. The bulk of the research that was done to study whether or not celiac disease and psoriasis could have a connection was flawed or biased in some way, which resulted in conclusions that could not be considered definitive. These flaws or biases included a small sample size, a lack of controls, a low accuracy of serological methods used to screen for celiac disease (i.e. anti-gliadin antibodies, AGAs), and the setting, including the design as single-centre studies. All of these issues contributed to the conclusion that the study was flawed or biased. Despite the fact that there is a connection between the two disorders, the physiopathologic mechanisms that are at the root of the connection between psoriasis and CD have not been fully explored. The presence of shared genes (at-risk HLA haplotypes), which are frequently taken into consideration when attempting to explain the increased incidence of CD in a number of autoimmune illnesses, could be present in people who have psoriasis, according to our working hypothesis. Psoriasis is a chronic inflammatory skin condition that can affect any part of the body. Although the results of the link between psoriasis and celiac disease based on the research that was conducted in 2010 are inconsistent, newer studies and studies that were conducted before 2010 provide evidence that there is a connection between the two conditions. Celiac disease is an autoimmune disorder that affects the small intestine and can cause psoriasis.